Career interests of students in psychology specialties degrees: psychometric evidence and correlations with the RIASEC dimensions - Ferreira, A. (2016)
In this study, we present the development of a vocational interest scale for university students studying psychology. Three dimensions were extracted through principal component analysis, namely, organizational, educational, and clinical psychology. A second study with confirmatory factor analysis replicated the same three factors obtained in the first study. We found significant positive correlations between clinical and educational psychology with the social dimension of Holland’s model. The enterprising dimension appeared to be significantly and positively correlated with the organizational psychology component. Implications and suggestions for future research are discussed.